2011
DOI: 10.1002/pssa.201127083
|View full text |Cite
|
Sign up to set email alerts
|

Role of energy level alignment in solar cells sensitized with a metal‐free organic dye: A combined experimental and theoretical approach

Abstract: We report results of combined experimental and theoretical studies of dye‐sensitized solar cells (DSSCs) using 5‐(4‐sulfophenylazo)salicylic acid disodium salt, known as Mordant Yellow 10 (MY‐10), as TiO2 sensitizer. We focus on a single dye but vary the solvent and the pH of the solution as well as the photoelectrode preparation conditions to determine the conditions for best photovoltaic conversion efficiency. We found experimentally that the efficiency, measured under standard air mass 1.5 global (AM 1.5G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…One possible explanation of this effect may be the hindering of the charge injection from the excited state of the dye to the conduction band of the oxide when the energy difference between the two is larger. The importance of the good matching between the electron donor (excited dye) and the acceptor (semiconductor conduction band) in order for injection to occur at a sufficiently rapid rate was previously mentioned by us [24,25,49] and other authors [46,47].…”
Section: Experimental Results and The Effect Of Extract Purificationmentioning
confidence: 91%
See 2 more Smart Citations
“…One possible explanation of this effect may be the hindering of the charge injection from the excited state of the dye to the conduction band of the oxide when the energy difference between the two is larger. The importance of the good matching between the electron donor (excited dye) and the acceptor (semiconductor conduction band) in order for injection to occur at a sufficiently rapid rate was previously mentioned by us [24,25,49] and other authors [46,47].…”
Section: Experimental Results and The Effect Of Extract Purificationmentioning
confidence: 91%
“…The values on the axes in Fig. 4 are relative to the vacuum (on the left axis) and to the normal hydrogen electrode (NHE, on the right axis) [24,25].…”
Section: Energy Level Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher performance of the dyes with both carboxy and hydroxy anchoring groups [28] has led us to revisit earlier studies of a dye with three types of anchoring groups: –OH, –COOH and –SO 3 H [2930]. We showed that although the salicylate does use both the carboxy and hydroxy substituent groups, the binding configuration is not bidentate chelate, as previously thought [14,1820].…”
Section: Introductionmentioning
confidence: 67%
“…Similarly, the binding of SA was thought as bidentate chelate through the oxygen atoms of –OH and of –COOH [14,20]. In a previous paper [29] we showed that for Mordant Yellow-10 anchoring through the SA part can lead to three binding modes, depending on the degree of deprotonation, but none of them was bidentate chelate. Returning to the present study, for SA we performed geometry optimization calculations in three cases.…”
Section: Resultsmentioning
confidence: 99%